Physiography the water shed of stream Coqueiro - Jataizinho, PR, obtained by geotechnical mens - Ribeiro, Fernanda Leite; Campos, Sergio [UNESP]; Traficante, Daniela Polizeli [UNESP]; Piva dos Santos, Willian Renam; Nardini, Rafel Calore (Univ Estadual Centro-oeste, 2015)
This study applies geoprocessing in morphometric characterization of the Stream Coqueiro watershed - Jataizinho, Stateof PR, through the Geographic Information System software - IDRISI Selva, aim ingat the preservation, rationalization of their use and environment al recovery. The water shed hasanarea of 1171,07ha and is located between the UTM coordinates, longitude 503037 to 510757m W and latitudes 7426,813 to 7429722m S. The cartographic base use dwere the cartographic mapsof Assam andUrai (PR), scale 1: 50000 (IBGE, 1991) in the extraction of contour lines, hydrography and topography, Geographic Information System environment - Idrisi Selva, to determine the morphometric in dices. The results showed that low levels of drainage densitya ssociate dwith the presence of permeable rock, facilitate the infiltration of the soil water run off and decreasing therisk of erosion and environment al degradation, as well as the low value of the shape factors upported by the circularity index indicates that the water shed tendstobe more elongate dwith les ssusceptibility to floods more pronounced. The environment al parametercoe fficient ofroughnessal low edto classify the water shed for vocation with forest and reforestation.
Keywords: Drainage network; geographic Information system; morphometry